Предмет: Геометрия,
автор: annaanna9992007
3(x-1)=2(x+2)
И это,если можно 3(x-5)-2(x+4)=-5x+1
Ответы
Автор ответа:
0
1) 3(х-1)=2(х+2)
3х-3=2х+4
3х-2х=4+3
х=7
2) 3(х-5)-2(х+4)=-5х+1
3х-15-2х-8=-5х+1
3х-2х+5х=15+8+1
6х=24
х=4
3х-3=2х+4
3х-2х=4+3
х=7
2) 3(х-5)-2(х+4)=-5х+1
3х-15-2х-8=-5х+1
3х-2х+5х=15+8+1
6х=24
х=4
Автор ответа:
0
3(х-1)=2(х+2)
3х-3=2х+4
3х-2х=3+4
х=7
Ответ:х=7
3(х-5)-2(х+4)=-5х+1
3х-15-2х-8=-5х+1
х+5х=1+15+8
6х=24
х=4
Ответ:х=4
3х-3=2х+4
3х-2х=3+4
х=7
Ответ:х=7
3(х-5)-2(х+4)=-5х+1
3х-15-2х-8=-5х+1
х+5х=1+15+8
6х=24
х=4
Ответ:х=4
Похожие вопросы
Предмет: Математика,
автор: kovylsvetik4853
Предмет: Математика,
автор: LpsNika6649
Предмет: Русский язык,
автор: Idoknow2344
Предмет: Математика,
автор: камилла230
Предмет: Математика,
автор: гпеаапаааоа